The Role of Honorary Agency of Board on Aceh House of Representatives (A Study of Policy Implementation Based on Aceh's DPR Regulation Number 02 of 2016 concerning the Ethics Code of the Aceh House of Representatives) - Muhammad; Syafei Ibrahim; Ismail (Budapest International Research and Critics University, 2020)
The Honorary Agency of Board has various roles in maintaining dignity in the interests of the state, nation and also every member of the board needs to be held responsible both in fact and in commission. Increased ability of Honorary Agency of Board to maintain dignity, especially prioritizing the interests of the state which is more oriented in the interests of individuals and groups in this case the bearer party to parliament. The method used in this study is qualitative, data collected through observation, interviews and analysis of documents that exist in Aceh House of Representatives. The results and conclusions of the study show that the role of Honorary Agency of Board in addressing the Behavior of Members of the Board of Aceh House of Representatives related to maintaining dignity, maintaining the honor and credibility of the board shows that The Honorary Agency of Board has a good role in terms of maintaining dignity for the interests of the State, Nation and prioritize a sense of responsibility in carrying out the mandate.